Analysis of Students' Speaking Skill Using Scaffolding Strategy: Analisis Keterampilan Berbicara Siswa Menggunakan Strategi Scaffolding - Ayu Kinasih; Dian Novita (Academia Open, 2022)
Based on observation made by the researcher of the eleventh grade student at SMAN 1 Porong, it discovered that students often find out difficulties while learning English, especially in speaking. These problems are faced by several factors such as unconfidently, lack of courage and seldom practiced. The implementation of scaffolding strategy in EFL learning might be an ideal solution to solve students’ poor speaking skill. This research aims to analyse students’ speaking ability after achieving the scaffolding strategy treatment. Under the descriptive quantitative method, the data were collected through students’ speaking performance. The sample comprised XI IPS 3 which consists of 34 students. The data were taken by giving speaking test in which students were required to retell their past experience after the teacher implemented scaffolding strategy. Here, the test assessed using five aspects of spoken language including pronunciation, grammar, vocabulary, fluency, and comprehension. The result of the study shows that 94 % out of 34 students have good performance in speaking.